Improving the care of people with dementia in general hospitals: evaluation of a whole-system train the trainer model - Sampson, Elizabeth L.; Vickerstaff, Victoria; Lietz, Stephanie; Orrell, Martin (Cambridge University Press, 2016)
Background: There are concerns about the quality of care that people with dementia receive in the general hospital. Staff report a lack of confidence and inadequate training in dementia care. Methods: A train-the-trainer model was implemented across eight acute hospital trusts in London via a large academic health and science network. Impact was evaluated using mixed methods. Data was collected at (a) Individual level: ‘Sense of Competence in Dementia Care’ (SCID) (b) Ward level: Person Interaction and Environment (PIE) observations (c) Organisation level: use of specific tools i.e. “This Is Me”, (d) Systems level: numbers and types of staff trained per trust. Results were analysed with descriptive statistics and paired t-test with thematic framework analysis for PIE observations. Results: Number of staff trained per trust ranged from 67 to 650 (total 2,020). 1,688 (85%) baseline questionnaires and 456 (27%) 3 month follow-up questionnaires were completed. Mean SCID score was 43.2 at baseline and 50.7 at follow-up (paired t-test, p<0.001). All sub-scales showed a small increase in competence, the largest being for ‘building relationships’. Organisational level data suggested increased use of carer’s passport, “This Is Me” documentation, dementia information leaflets, delirium screening scales and pathways. PIE observations demonstrated improved staff-patient interactions but little change in hospital environments. Conclusions: There was a significant improvement in staffs’ sense of competence in dementia care and the quality of interactions with patients. More hospitals adopted person centred tools and pathways. Work is required to investigate if these changes improve hospital outcomes for people with dementia.